Polycystic Ovary Syndrome: Insights from Preclinical Research. Issue 8 (25th August 2022) - Reckelhoff, Jane F.; Shawky, Noha M.; Romero, Damian G.; Yanes Cardozo, Licy L.
Abstract : Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, affecting approximately 10%. PCOS is diagnosed by the presence of at least two of these three criteria: hyperandrogenemia, oligo- or anovulation, and polycystic ovaries. The most common type (80%) of PCOS includes hyperandrogenemia. PCOS is also characterized by obesity or overweight (in 80% of US women with PCOS), insulin resistance with elevated plasma insulin but not necessarily hyperglycemia, dyslipidemia, proteinuria, and elevated BP. Although elevated compared with age-matched controls, BP may not reach levels considered treatable according to the current clinical hypertension guidelines. However, it is well known that elevated BP, even modestly so, increases the risk of cardiovascular disease. We have developed a model of hyperandrogenemia in rodents that mimics the characteristics of PCOS in women, with increases in body weight, insulin resistance, dyslipidemia, andproteinuria and elevated BP. This review discusses potential mechanisms responsible for the elevated BP in the adult and aging PCOS rat model that may be extrapolated to women with PCOS.